Substrate and Topsoil Impact on Soil Water and Soil Temperature in Arctic Diamond Mine Reclamation - Amalesh Dhar; Valerie S. Miller; Sarah R. Wilkinson; M. Anne Naeth (Soil Systems, 2022)
Soil properties in the Arctic are insufficiently explored and documented, particularly extensive monitoring of soil water and soil temperature over a period of time. Soil water and soil temperature are critical for understanding land surface and atmosphere interactions and are considered key factors for revegetation during mine reclamation. This study assessed how substrate and topsoil influenced soil temperature and soil water content at a reclaimed diamond mine in the Northwest Territories of Canada. Three substrates (crushed rock, processed kimberlite, and lake sediment) with and without topsoil were used. Mean air temperature changed little from year to year, although summer temperature showed a slightly increasing trend. Both annual and summer precipitation sharply declined over time. Soil water was influenced more by substrate than by placing 10 cm of topsoil on it. Processed kimberlite had greater water retention characteristics and water content than lake sediment and crushed rock substrates (significantly). Surface soil water content was lower with than without topsoil, suggesting that 10 cm of topsoil was not enough to influence it. Soil temperatures were not influenced by either substrate or topsoil. This study suggests processed kimberlite could be used as a substrate component for water and temperature management during reclamation of this extreme environment.